2015
DOI: 10.1016/j.stemcr.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences between GDNF-Dependent and FGF2-Dependent Mouse Spermatogonial Stem Cell Self-Renewal

Abstract: SummarySpermatogonial stem cells (SSCs) are required for spermatogenesis. Earlier studies showed that glial cell line-derived neurotrophic factor (GDNF) was indispensable for SSC self-renewal by binding to the GFRA1/RET receptor. Mice with mutations in these molecules showed impaired spermatogenesis, which was attributed to SSC depletion. Here we show that SSCs undergo GDNF-independent self-renewal. A small number of spermatogonia formed colonies when testis fragments from a Ret mutant mouse strain were transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 40 publications
8
113
1
Order By: Relevance
“…In previous studies, we found that ID4-EGFP + spermatogonia are also GFRA1 + (Chan et al, 2014). In the current study, our transcriptome analyses demonstrate that Gfra1 expression is significantly upregulated in ID4-EGFP Bright SSCs; and a previous study found that levels of GFRA1 are positively associated with colonization activity in a transplantation assay (Takashima et al, 2015), although the potency is considerably less than that of the ID4-EGFP Bright population. Thus, it is likely that spermatogonia expressing high levels of GFRA1 are the true SSCs and those with lower levels are immediate progenitors.…”
Section: Discussionsupporting
confidence: 68%
“…In previous studies, we found that ID4-EGFP + spermatogonia are also GFRA1 + (Chan et al, 2014). In the current study, our transcriptome analyses demonstrate that Gfra1 expression is significantly upregulated in ID4-EGFP Bright SSCs; and a previous study found that levels of GFRA1 are positively associated with colonization activity in a transplantation assay (Takashima et al, 2015), although the potency is considerably less than that of the ID4-EGFP Bright population. Thus, it is likely that spermatogonia expressing high levels of GFRA1 are the true SSCs and those with lower levels are immediate progenitors.…”
Section: Discussionsupporting
confidence: 68%
“…GDNF can activate the PI3K/AKT pathway by binding to the GDNF receptor components GFRA1 and RET to stimulate SSC/SPC proliferation (Lee et al 2007, Oatley et al 2007). FGF2 can also significantly increase SSC/ SPC proliferation (Ishii et al 2012), whereas the balance between the FGF2 and GDNF levels mediates SSC selfrenewal, as an increased level of GDNF associated with an elevated stem cell number is observed in FGF2-depleted testes (Takashima et al 2015). In addition to stimulating self-renewal, Sertoli cells are the main source of RA in mouse testes.…”
Section: Extrinsic Stimulation and Ssc/spc-associated Microenvironmentsmentioning
confidence: 99%
“…Comparing to prospermatogonia, postnatal SSC/SPCs are more heterogeneous, even within subpopulations with identical surface markers, for instance GFRA1 C , PLZF C and THY1 C SSC/SPCs (Kubota et al 2003, Gassei & Orwig 2013, Hermann et al 2015, Takashima et al 2015. The differences in isolation protocols and the affinity of antibodies may have effects on the enrichments of subpopulations with specific cellular states (Buageaw et al 2005, Ebata et al 2005, Grisanti et al 2009, Hermann et al 2015, Takashima et al 2015, Vlachogiannis et al 2015.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice and human, SSCs self-renewal is stimulated by Glial cell lineDerived Neurotrophic Factor (GDNF) through the sertoli cells, and Fibroblast Growth Factor 2 (FGF2) is expressed in Leydig cells which interacts with GDNF to enhance proliferation rate of SSCs [39]. According to previous reports, around 50% of the SSCs populations endured selfrenewal through GDNF, whereas reaming 50% will further differentiate into spermatogonia to continue production of spermatozoa through FGF2 and GDNF interaction [52,53]. In addition the controlling of the endocrine and local signaling system, some miRNAs are also involved in regulation and differentiation of .…”
Section: Micrornas and Spermatogonial Stem Cellsmentioning
confidence: 99%